Norepinephrine-Induced Adrenergic Activation Strikingly Increased the Atrial Fibrillation Duration through β1- and α1-Adrenergic Receptor-Mediated Signaling in Mice - Suita, Kenji; Fujita, Takayuki; Hasegawa, Nozomi; Cai, Wenqian; Jin, Huiling; Hidaka, Yuko; Prajapati, Rajesh; Umemura, Masanari; Yokoyama, Utako; Sato, Motohiko; Okumura, Satoshi; Ishikawa, Yoshihiro (PLOS ONE, 2015)
Background Atrial fibrillation (AF) is the most common arrhythmias among old people. It causes serious long-term health problems affecting the quality of life. It has been suggested that the autonomic nervous system is involved in the onset and maintenance of AF in human. However, investigation of its pathogenesis and potential treatment has been hampered by the lack of suitable AF models in experimental animals. Objectives Our aim was to establish a long-lasting AF model in mice. We also investigated the role of adrenergic receptor (AR) subtypes, which may be involved in the onset and duration of AF. Methods and Results Trans-esophageal atrial burst pacing in mice could induce AF, as previously shown, but with only a short duration (29.0±8.1 sec). We found that adrenergic activation by intraperitoneal norepinephrine (NE) injection strikingly increased the AF duration. It increased the duration to more than 10 minutes, i.e., by more than 20-fold (656.2±104.8 sec; P<0.001). In this model, a prior injection of a specific β1-AR blocker metoprolol and an α1-AR blocker prazosin both significantly attenuated NE-induced elongation of AF. To further explore the mechanisms underlying these receptors’ effects on AF, we assessed the SR Ca2+ leak, a major trigger of AF, and consequent spontaneous SR Ca2+ release (SCR) in atrial myocytes. Consistent with the results of our in-vivo experiments, both metoprolol and prazosin significantly inhibited the NE-induced SR Ca2+ leak and SCR. These findings suggest that both β1-AR and α1-AR may play important roles in the development of AF. Conclusions We have established a long-lasting AF model in mice induced by adrenergic activation, which will be valuable in future AF study using experimental animals, such as transgenic mice. We also revealed the important role of β1- and α1-AR-mediated signaling in the development of AF through in-vivo and in-vitro experiments.